The relationship between bronchoalveolar lavage fluid cytology and airway hyper‐reactivity in a population of Australian horses presented for poor performance. Issue 9 (8th July 2019) - Secombe, CJ; van Eps, AW; Bruce, M; Lester, GD
Abstract : Objective: To investigate the relationship between bronchoalveolar lavage fluid cytology, particularly mast cells, and airway hyper‐reactivity in athletic horses presented for poor performance that included a respiratory tract evaluation in two disparate locations in Australia. Design: Multi‐centre, retrospective and prospective cross‐sectional study Methods: Eighty four adult horses underwent both pulmonary function testing and histamine bronchoprovocation with a commercial flowmetric plethysmography system. A bronchoalveolar lavage was performed four to twelve hours later. Bronchoalveolar lavage fluid cytology was categorised using two differing classification systems to define mild equine asthma. Statistical analysis was used to assess associations between bronchoalveolar lavage fluid relative inflammatory cell percentages, and airway hyper‐reactivity and their associated categorisations. Results: Sixty four percent (54/84) of horses displayed airway hyper‐reactivity, as defined by PC35  < 6 mg/ml of histamine. A relative mastocytosis was the most common bronchoalveolar lavage fluid cytological abnormality. Horses with a sole mast cell response of ≥ 5% within their bronchoalveolar lavage fluid displayed airway hyper‐reactivity at a lower dose of nebulized histamine than horses with normal bronchoalveolar lavage fluid cytology. Horses with mixed cell responses (relative mast cell percentage > 2% and/or relative neutrophil percentage > 5% and/or eosinophil relative cell percentage ≥ 1%) displayed airway hyper‐reactivity at a lower dose of nebulized histamine than horses with normal bronchoalveolar lavage fluid cytology. Conclusion: In the Australian context, recently revised increased bronchoalveolar lavage fluid cytology relative cell percentage cut offs appear appropriate for sole mast cell responses. The historical lower cut offs appear to be appropriate for mixed inflammatory cell responses.